Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/vms3.555
|View full text |Cite
|
Sign up to set email alerts
|

New aspects of the esophageal histology of the domestic goat (Capra hircus) and European roe deer (Capreolus capreolus)

Abstract: The present study examines the esophageal wall of animals from two distinct families of the Ruminantia: domestic goats and European roe deer. Five fragments were collected from the entire length of the esophageal wall in five goats and four roe deer and subjected to microscopic and morphometric analyses. All layers of the esophageal wall except the tela submucosa were found to be thicker in the goats. In both species, the esophagus was lined by parakeratinized stratified squamous epithelium, and the tela submu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The muscle fibers were oriented longitudinally, the exact orientation of the folds of the mucosa. These results were compatible with the results of Sokolowska (32).…”
Section: Discussionsupporting
confidence: 93%
“…The muscle fibers were oriented longitudinally, the exact orientation of the folds of the mucosa. These results were compatible with the results of Sokolowska (32).…”
Section: Discussionsupporting
confidence: 93%
“…Our finding revealed that the tunica mucosa of the esophagus was lined by non-keratinized stratified squamous epithelium with increased thinning at the abdominal part of the esophagus. The non-keratinized esophageal epithelium was recorded in dogs and humans [ 17 ] and guinea pigs [ 21 ], while the equine [ 20 ], goats [ 22 , 23 ], and guinea pig [ 24 ] possess a keratinized type. Our results denoted significant differences in esophageal tunicae thickness along the entire regions of the esophagus.…”
Section: Discussionmentioning
confidence: 99%
“…Several insectivorous–omnivorous rodents do not have epithelial keratinisation (Borghesi et al, 2015; Igbokwe & Obinna, 2016; Oliver et al, 2010), whereas the keratinized layer can be found in herbivorous rodents that consume mainly grass and rough plant material (Kotźe et al, 2006; Scopin et al, 2015; Tammam et al, 2017). Like its relative, S. leucodon , C. badius possessed a keratinized epithelium, which may protect the oesophageal mucosa from food abrasion (Scopin et al, 2015; Sokołowska et al, 2021), bacteria invasion (Squier & Kremer, 2001) and gastric juice during regurgitation (if present).…”
Section: Discussionmentioning
confidence: 99%